PELATIHAN PENANAMAN TANAMAN HIDROPONIK SEBAGAI UPAYA PEMBERDAYAAN KELOMPOK PKK DI DESA KALITENGAH KABUPATEN LAMONGAN - Muhammad Fachrizal Hamdani; Muhammad Alfian Pratama; Atilla Dani Putra; Shalsabilla Bayu Razilda; Ridhoatin Khoiriyah; Dilla Amalia Bilqis Ikhsan; Gladia Renata Putri; Christian Gultom; Muhammad Zaid Mustofa; Shania Vivi Armylia Putri (LP2M Universitas Ibrahimy, 2023)
This community service activity was carried out with the aim of introducing and implementing a hydroponic plant system in Kalitengah Village through training activities. This was due to the potential that Kalitengah Village had, namely the enthusiasm of the Kalitengah Village community, especially the PKK group, for planting activities. The limited land of each resident's house was also the reason why hydroponic planting activities could be carried out. The method of this activity was socialization and training. The socialization was carried out as a method for delivering material about hydroponics, while the training was carried out as a method for practicing hydroponic plant nurseries, one of which was green lettuce. The results of this activity were seen through indicators of activity success. In general, this activity was attended by 60% of the total invitees. The participants took part in this activity with a high level of enthusiasm from the start of delivering the material to nursery practice. Through this training activity, the people of Kalitengah Village could immediately plant hydroponic plants without supervision from the KKN group so that this activity had a sustainable value.